Socio-Economic Impact on the Sinamot Tradition from an Islamic Law Perspective (Analysis Study of Batak Tribe Customs in Padang Gelugur District, Pasaman Regency) - Nurul Hasanah (al-Afkar, Journal For Islamic Studies, 2025)
Marriage is a fundamental social institution for humans, and almost all religious and cultural teachings regulate its implementation carefully. In Islam, marriage is not only seen from an essential perspective, namely to fulfill God's commands, but also from an ethical perspective, namely to respect and protect women's rights. One of the important elements in an Islamic wedding is the dowry, which serves as a sign of sincerity and respect for the bride. However, apart from religious teachings, cultural values and customs also play a significant role in people's lives. For example, in Padang Gelugur sub-district there is a "sinamot" tradition which is similar to the concept of dowry in Islam. This sinamot money is given before the wedding and is intended as a form of respect for the bride. Even though the purpose is similar to dowry, it is different from dowry. From the perspective of Islamic law, it is important to assess whether the sinamot money tradition is in line with the principles set out in Islam. Essentially, both dowry and sinamot money function to show seriousness and commitment to the marriage, as well as to respect and provide guarantees to the bride. In this research the author focuses on two things, namely how sinamot money is practiced and how sinamot money is reviewed in Islamic law. In the research the author used a qualitative method which helped the author analyze people's customary behavior, using a juridical sociological approach. In the research, the author found that the terms of sinamot money were determined by deliberation between the two parties, and in the analysis in Islamic law, it was in accordance with the theory, namely Maqasid Syari'ah.